Problems and challenges of automating cataloguing process at Kenneth Dike Library, University of Ibadan, Nigeria (2002)
This paper discusses the problems faced by Kenneth Dike Library in automating its cataloguing process since 1992. It further attempts to identify some of the constraints inhibiting the success of the process: inadequate funding, dearth of systems analysts, absence of dedicated commitment to automation on the part of the library management. There are some of the issues discussed. It concludes by proffering some solutions that could ameliorate the problems posed.